CRP – a valuable source of information or just a laboratory test? - Leszcz, Monika; Więckowska-Deroń, Marta; Nitka, Karolina; Białek, Justyna; Ćwik-Błotnicka, Dominika; Borczyk, Joanna (Journal of Education, Health and Sport, 2023)
Background and Purpose: Laboratory tests are an inseparable element in modern medicine. They provide us with valuable clues for making a diagnosis or monitoring treatment. One of the most frequently ordered biochemical tests is the determination of the level of CRP in the blood. The aim of the study is to present the clinical usefulness of this study and to present knowledge about C-reactive protein. Current state of knowledge: It is produced mainly by the liver, but the latest reports confirm local synthesis, among others, in arterial endothelial cells. The most common reason for the increase in the level of CRP is the appearance of infection, during which time its concentration may increase by up to 1000 times. Elderly patients have a weaker immune system response than younger patients, therefore the rise in CRP may be less pronounced. Other reasons are autoimmune diseases, cancer, or acute or chronic inflammation. As a result of cel damage, pro-inflammatory cytokines are secreted, which stimulate the production of CRP. Most scientific sources consider CRP ≥ 10 mg/L to be significant. Values of 3-10mg/L are considered a slight increase in CRP levels. Such CRP values were found in about 1/3 of the American population. Conclusions: The CRP level should not be interpreted as an isolated medical parameter, but in conjunction with other tests and the patient's current state of health. Based on the amount of CRP in the blood and changes in its concentration over time, we can check the response to treatment and predict the course of some diseases.